2010
DOI: 10.3109/09638281003734482
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ambulatory step activity, self-reported physical functioning and standardised timed walking in patients with haematological malignancies

Abstract: N K (2010). The relationship between ambulatory step activity, self-reported physical functioning and standardised timed walking in patients with haematological malignancies. Disability and Rehabilitation, 32(22):1819-1826. Postprint available at: http://www.zora.uzh.ch Similarly, ambulatory activity monitoring did not correlate significantly with self-reported functional status in patients with chronic obstructive pulmonary disease. [20] To the best of our knowledge, only one previous report has investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The weak association between the pro-pf and cardiorespiratory fitness is in line with results of two earlier studies that showed a weakly-to-moderately significant positive correlation between the pro-pf and the 6-minute walk test in patients with cancer 12,14 . The association between the pro-pf and objectively measured physical activity in patients with cancer has also been investigated in three previous studies, two of which found a weakly-to-moderately significant association 12,13 ; another study found no significant association 18 . The strength of our study lies in its evaluation of both associations in the same large population of patients with cancer and the use of "gold standard" objective assessments.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The weak association between the pro-pf and cardiorespiratory fitness is in line with results of two earlier studies that showed a weakly-to-moderately significant positive correlation between the pro-pf and the 6-minute walk test in patients with cancer 12,14 . The association between the pro-pf and objectively measured physical activity in patients with cancer has also been investigated in three previous studies, two of which found a weakly-to-moderately significant association 12,13 ; another study found no significant association 18 . The strength of our study lies in its evaluation of both associations in the same large population of patients with cancer and the use of "gold standard" objective assessments.…”
Section: Discussionsupporting
confidence: 90%
“…If agreement is sufficient, the pro-pf could be used instead of time-consuming and expensive objective measurements of physical activity (with accelerometers, for instance) and fitness (with the maximal exercise test). Earlier studies showed that the association between the pro-pf and physical activity 12,13 and between the pro-pf and cardio respiratory fitness (assessed using the submaximal 6-minute walk test) 12,14 was weak to moderate (Pearson correlation coefficients: 0.33-0.55). However, those studies did not investigate the interrelationships of the pro-pf and physical activity and cardiorespiratory fitness in the same sample, hampering a direct comparison.…”
Section: Introductionmentioning
confidence: 99%
“…The median VO 2peak for our group of 20.9 mL/kg/min compares with a VO 2peak of 22.8 mL/kg/min in independently living 55-86-year-old men. 26 Patients in our cohort walked a pre-HCT median of 480 m (range 305-690 m), compared with a reported mean 6MW distance of 575.8 m in other patients with hematological malignancies, 27 and a mean of 384 m in post-allogeneic HCT patients. 21 The 6MW distance has demonstrated prognostic value in other clinical populations, including patients with chronic obstructive pulmonary disease or heart failure, older adults and those with solid tumors, hematological malignancies and post-transplant survivors.…”
Section: Discussionmentioning
confidence: 99%
“…One randomized study in HCT patients reported differences in some objective measures of strength and endurance, but not in self-reported symptoms or QOL, suggesting that the detected functional differences were not clinically meaningful 49 or that these measures are not reflective of physical functioning. 50 The SF-36 PCS and MCS are global subscales that may not capture improved strength or endurance. However, the CTXD was developed specifically to measure distress related to HCT, and it has shown sensitivity to change over the course of treatment.…”
Section: Discussionmentioning
confidence: 99%